2006
DOI: 10.4161/cc.5.6.2573
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian Cyclin D1/Cdk4 complexes induce cell growth in Drosophila

Abstract: ABBREVIATIONS ReportMammalian Cyclin D1/Cdk4 Complexes Induce Cell Growth in Drosophila ABSTRACTThe Drosophila melanogaster cyclin dependent protein kinase complex CycD/Cdk4 has been shown to regulate cellular growth (accumulation of mass) as well as proliferation (cell cycle progression). In contrast, the orthologous mammalian complex has been shown to regulate cell cycle progression, but possible functions in growth control have not been addressed directly. To test whether mammalian Cyclin D1/Cdk4 complexes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Bearing in mind the morphology of the cells that accumulated cyclin D1 and only faint, dispersed staining in the cells with SAHF, it may also be hypothesized that sequestration probably serves the special purpose of inactivation of the protein on a cellular route to senescence. However, the phenomenon requires a more in-depth revision, especially in face of the fact that mammalian cyclin D1/Cdk4 complexes have been proven to contribute to endoreduplication, most probably via the stimulation of nucleoli enlargement and ribosomal biogenesis [59]. In our study the nuclei of polyploid cells showed often intense cyclin D1 staining, sometimes accompanied by intranucleolar aggregations as well.…”
Section: Discussionmentioning
confidence: 58%
“…Bearing in mind the morphology of the cells that accumulated cyclin D1 and only faint, dispersed staining in the cells with SAHF, it may also be hypothesized that sequestration probably serves the special purpose of inactivation of the protein on a cellular route to senescence. However, the phenomenon requires a more in-depth revision, especially in face of the fact that mammalian cyclin D1/Cdk4 complexes have been proven to contribute to endoreduplication, most probably via the stimulation of nucleoli enlargement and ribosomal biogenesis [59]. In our study the nuclei of polyploid cells showed often intense cyclin D1 staining, sometimes accompanied by intranucleolar aggregations as well.…”
Section: Discussionmentioning
confidence: 58%
“…Importantly for this study, overgrowth induced by ectopic expression of Cyclin D/Cdk4 is insensitive to nutrient conditions [49], demonstrating that the Cyclin D/Cdk4 pathway is nutrient-responsive. We now show that ectopic expression of Cyclin D/Cdk4 in the larval fat body is sufficient to drive mitochondrial abundance in a Delg-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 67%
“…This model is attractive because early activation of cdk2 might cause premature phosphorylation of its substrates and force the G 1 -S phase transition to occur before its time. As cyclin D-cdk4 activity has also been linked to growth control, at least in Drosophila, 45,46 activation of those substrates might also be required to ensure that the smaller G 0 arrested cell is physically ready to enter the cell cycle.…”
Section: © 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%